2005
DOI: 10.1016/j.ejpain.2004.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence and predictors among inpatients in a major Italian teaching hospital. A baseline survey towards a pain free hospital

Abstract: Pain prevalence among inpatients is an important indicator of quality care; it may reach over 80% in various clinical settings. A cross-sectional survey was conducted in a teaching hospital to depict benchmark data regarding pain prevalence and predictors among the entire inpatient population. Overall 892 patients, 6 years old and hospitalized for at least 24 h in 57 hospital wards were interviewed using an internationally applied questionnaire. Patients self-reported their pain intensity at the time of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 25 publications
9
83
1
4
Order By: Relevance
“…The idea of a pain-free hospitalization as a cornerstone of a core set of measures designed to evaluate the quality of health-care delivery and inform quality improvement is becoming a reality in health care (1)(2)(3). Many of these hospital initiatives are directed at post-operative pain, palliative pain and oncologic pain.…”
Section: Commentary By Todd J Kilbaughmentioning
confidence: 99%
“…The idea of a pain-free hospitalization as a cornerstone of a core set of measures designed to evaluate the quality of health-care delivery and inform quality improvement is becoming a reality in health care (1)(2)(3). Many of these hospital initiatives are directed at post-operative pain, palliative pain and oncologic pain.…”
Section: Commentary By Todd J Kilbaughmentioning
confidence: 99%
“…Recent literature data has shown that over 50% of hospitalized patients complained of moderate to severe pain in the previous 24 hours, regardless of cause (surgical, neoplastic, traumatic, other) [15][16] . Some authors 9,17 assessed pain at two times of hospital admission, during the interview and the previous 24 hours and found the prevalence of 23%-64% 9 and 38%-52% 17 , respectively. In this study, we found an overall prevalence of 31.8% of pain during the interview (mean of 6.6 in NRS), with strong/severe pain in 44.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Malgré ces progrès, les niveaux de prévalence des douleurs dans les institutions de soins restent pré-occupants, allant de 40 à 80 % selon les lieux [16,23,27,29,30,35,36,46,47].…”
Section: Introductionunclassified